HUBUNGAN ANTARA RASA AMAN DENGAN MINAT BELAJAR SISWA KELAS IV SEKOLAH DASAR NEGERI 109 PEKANBARU - Imam Hariadi; Syahrilfuddin Syahrilfuddin; Hendri Marhadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: The problem in this research starts from the observation of researchers who saw a sense of security provided by the teacher, researchers are trying to determine their effect on learning interest of students in schools. This study was done to determine the relationship between security interests fourth grade students of State Elementary School 109 Pekanbaru. This research is a correlation study (Study correlational) or correlation study. The population in this research were 67 students, using saturation sampling technique is the entire population of the sample djadikan didapatlah sample of 67 students. The instrument used to collect data that researchers use a questionnaire that first tested the validity and reliability by using SPSS version 17.0. to test the normality of the data, researchers used chi-squared test. Furthermore, to know relationship between a sense of security (X) with students' learning interest (Y) used formula Pearson Product Moment Correlation. From the analysis of the data is obtained no significant relationship between the security interests students of class IV State Primary School 109 Pekanbaru obtained from the results of significant test for correlation of security with student interest there is value Thitung ≥ Ttabel = 1.040 ≤ 1.671 so it can be said that there was no significant relationship between the security interests students of class IV SDN 109 Pekanbaru.Keywords: Safety, Student Interest